2019
DOI: 10.17583/rimcis.2019.4147
|View full text |Cite
|
Sign up to set email alerts
|

Siege of Violent Crimes through Economic Complexity and Institutions

Abstract: This study is an effort to explore the determinants of violent crimes by using the panel data of 34 countries covering the time span from 2000 to 2014. The robust least square technique is applied for empirical analysis. The findings of the study reveal that the economic complexity, institutions and per capita income have significant negative impact while economic misery and population growth have significant positive relationship on violent crimes. Moreover, efficient institutions have prime importance to cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…According to Janko & Popli (2015), an increase in the rate population of men aged 8-44 years) will lead to an increase in the crime. The result supports the study of (Madni & Khan, 2019) who found the positive relationship between population growth and crime. Our study's finding also consistent with Briseño and Rojas (2020) who found that the changes in electricity theft in Mexico are determined by changes in population.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…According to Janko & Popli (2015), an increase in the rate population of men aged 8-44 years) will lead to an increase in the crime. The result supports the study of (Madni & Khan, 2019) who found the positive relationship between population growth and crime. Our study's finding also consistent with Briseño and Rojas (2020) who found that the changes in electricity theft in Mexico are determined by changes in population.…”
Section: Resultssupporting
confidence: 91%
“…Most cases of crime in Malaysia include motor vehicle theft, burglary, snatch theft, and violent crime (Ghani, 2017). The level of crime has been associated with various factors including economy complexity (Madni & Khan, 2019), the inefficiency of the institution (Madni & Khan, 2019), inflation (Tang, 2009;Gillani, Rehman & Gill, 2009), unemployment (Janko & Popli, 2015), population (Boatner, 2019;Briseño & Rojas, 2020;Madni & Khan, 2019), urbanization (Bennett, 1991;Briseño & Rojas, 2020;Ghani, 2017) and migration (Sidhu, 2005).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…It is signi cant at 10% level of signi cance. The inference is also shows consistency with Hidalgo and Hausmann (2009) and Madni and Khan (2019).…”
Section: Empirical Findings and Their Descriptionsupporting
confidence: 59%
“…(Marshall and Clark 1952). The subject of crime has gained a great deal of attention and is still an emerging and burning issue in contemporary research work ( Madni and Khan (2019) highlighted that the criminals commit a crime due to domestic con ict, economical tightness and due to social anxieties. A number of researchers have sought to investigate the intricate relationship between crime and economics.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of Madni and Khan (2019) study revealed that economic complexity, institutions, and per capita income have a significant negative impact while economic misery and population growth have a significant positive relationship on violent crimes using the panel data of 34 countries covering the time span from 2000 to 2014. Moreover, efficient institutions have prime importance to curb crimes in a society.…”
Section: Literature Reviewmentioning
confidence: 99%